Endometriosis experience infertility services. - Pacheco, José (2015)
OBJECTIVE: To review cases of endometriosis found at laparoscopy or laparotomy in women evaluated for infertility or recurrent abortion. DESIGN; Descriptive retrospective cross-sectional study. MATERIALS AND METHODS: 675 women with infertility or recurrent abortion underwent laparotomy or laparoscopy. PLACE: Human Reproduction Service National Hospital Edgardo Rebagliati Martins EsSalud. RESULTS: The prevalence of endometriosis was 47% (317 patients), being more frequent in women between 30 and 39 years. Endometriosis was minimal in seven cases (2.2%), mild in 101 (31.9%), moderate in 128 (40.4%) and severe in 81 cases (25.6%). In 38 cases one or more endometriosis was found. The most frequent location was posterior fornix, uterosacral ligament and the ovarian surface. It is also found in chronic salpingitis 26% (81 cases), with hydrosalpinges in 20 cases. They hatched 55 patients (17.4%), emphasizing that the monitoring was not optimal. CONCLUSIONS: The frequency of endometriosis is higher in women with infertility or recurrent abortion. The diagnosis of the disease has been in this review by laparoscopy and laparotomy interventions during which the flare of the lights and the removal of endometriomas is done and smooth adhesions and the functional anatomy of the fallopian tubes is restored .